The Psychodidae (Diptera) of Jaú National Park (Amazonas, Brazil) with description of two new species of Psychodinae - Cordeiro, Danilo Pacheco; Silva De Aquino, Karina Kethelen; Alves, Veracilda Ribeiro (Zootaxa, 2021)
The Jaú National Park, located in the Amazon, is the largest National Park of Brazil and still its insect fauna is barely known. Herein we describe two new species of Psychodinae, Alepia iy sp. nov. and Parasetomima timmirima sp. nov., and report 19 other species of Psychodidae, subfamilies Phlebotominae, Psychodinae and Trichomyiinae collected from this Conservation Unit. Micrommatos Quate & Brown, represented by M. stephaniae Quate & Brown, and Platyplastinx culmosus Quate & Brown are recorded for the first time for Brazil. Among the collected phlebotomine sand fly species, three species have previously been implicated in transmission of Leishmania: Nyssomyia anduzei (Rozeboom), Psychodopygus ayrozai (Barretto & Coutinho) and Trichophoromyia ubiquitalis (Mangabeira).